2018
DOI: 10.1002/ece3.4383
|View full text |Cite
|
Sign up to set email alerts
|

Root exudation rate as functional trait involved in plant nutrient‐use strategy classification

Abstract: Plants adopt a variety of life history strategies to succeed in the Earth's diverse environments. Using functional traits which are defined as “morphological, biochemical, physiological, or phonological” characteristics measurable at the individual level, plants are classified according to their species’ adaptative strategies, more than their taxonomy, from fast growing plant species to slower‐growing conservative species. These different strategies probably influence the input and output of carbon (C)‐resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 49 publications
2
69
0
Order By: Relevance
“…In addition, we found that root exudation per unit root biomass increased with SRL – which was also found in a recent study by Guyonnet et al . ()), although they did not express root exudation per unit root biomass – but root exudation only weakly predicted root‐exudate‐induced respiration at the 2 wk recovery harvest (Fig. S3).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that root exudation per unit root biomass increased with SRL – which was also found in a recent study by Guyonnet et al . ()), although they did not express root exudation per unit root biomass – but root exudation only weakly predicted root‐exudate‐induced respiration at the 2 wk recovery harvest (Fig. S3).…”
Section: Discussionmentioning
confidence: 99%
“…These strategies are reflected in their allocation of resources to root exudates; for instance, the fast‐growing grassland species Glyceria maxima exuded more C than the conservative Carex acuta (Kaštovská et al ., ). More recently, exudation has been proposed to be a functional root trait in its own right (Guyonnet et al ., ) and is also reflective of root traits such as specific root length, being positively correlated with increased C exudation. However, these studies did not take into account the quality (i.e.…”
Section: Root Exudates As Drivers Of Ecosystem Responses To Droughtmentioning
confidence: 99%
“…Leaf and root traits often show coordinated variation in stoichiometry and tissue density ( 5 ) (Freschet et al, ), but traits relating to root morphology can be a secondary, and potentially independent dimension of root trait variation ( 4 ) (Kramer‐Walter et al, ) as we observed in this study (see Figure ). The fast–slow spectrum can drive relative growth rates ( 6, 7, 8 ) (Reich, ; Wright et al, ) and root morphology may drive patterns of C allocation above‐ and below‐ground ( 14 , 15 ) (Guyonnet et al, ; Lange et al, ) and thus collectively standing biomass above‐ and below‐ground, while relative investment of growth above‐ versus below‐ground can drive root to shoot ratios ( 16 ) (Kimball et al, ). The fast–slow leaf spectrum can drive the relative importance of fungal versus bacterial dominated energy channels below‐ground ( 2, 9 ) (Legay et al, ), while patterns of plant C allocation below‐ground in terms of root length and root diameter may impact on root colonization rates and patterns of C exudation with consequences for microbial community structure ( 13 ) (Lange et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, increasing plant functional trait diversity has been proposed as a potential mechanism by which to increase carbon (C) allocation and storage below-ground (De Deyn, Cornelissen, & Bardgett, 2008). Root traits have been linked with below-ground C inputs (Guyonnet, Cantarel, Simon, & Haichar, 2018), decomposition rates (Freschet, Aerts, & Cornelissen, 2012;Smith, Woodin, Pakeman, Johnson, & Wal, 2014), soil C storage (Lange et al, 2015) and soil physical properties (Gould, Quinton, Weigelt, De Deyn, & Bardgett, 2016), which have wider implications for soil functioning. Despite these advances, there remains considerable uncertainty as to which plant functional traits (aboveground and/or below-ground) best predict soil properties and ecosystem processes.…”
Section: Introductionmentioning
confidence: 99%